2020
DOI: 10.1021/acs.jproteome.0c00326
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Informatics for Understanding Phases and Identifying Biomarkers in COVID-19 Disease

Abstract: The emergence of novel coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 coronavirus, has necessitated the urgent development of new diagnostic and therapeutic strategies. Rapid research and development, on an international scale, has already generated assays for detecting SARS-CoV-2 RNA and host immunoglobulins. However, the complexities of COVID-19 are such that fuller definitions of patient status, trajectory, sequelae, and responses to therapy are now required. There is accumulating evidence—fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 97 publications
1
75
0
1
Order By: Relevance
“…Over the past several months, proteomic and metabolomic profiles of peripheral blood samples have been investigated to correlate disease severity of COVID-19 with certain proteins and lipids. 54 , 55 Details can be found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several months, proteomic and metabolomic profiles of peripheral blood samples have been investigated to correlate disease severity of COVID-19 with certain proteins and lipids. 54 , 55 Details can be found elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, proteomic methods allowed the characterization and understanding of SARS-CoV during the severe acute respiratory syndrome (SARS) outbreak in 2003, enabling the description of virus protein sequences and antigenic virus proteins and the identification of ACE2 as the human receptor for SARS-CoV (Krokhin et al, 2003;Li et al, 2003;Ying et al, 2004). Consequently, the application of proteomic workflows may be highly beneficial to increase our understanding of the pathogenesis of COVID-19, to identify potential therapeutic targets, and even to develop fast and effective diagnostic tests (Struwe et al, 2020;Whetton et al, 2020). In this mini-review, we focus on different proteomic methodologies currently used to decipher novel SARS-CoV-2 targets and potential COVID-19 biomarkers ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…While our approach did find some associations in our mined COVID-19 corpus, our data mining in Coronavirus- and other related lung-damaging diseases as a proxy for COVID-19 produced valid comparators in terms of drug targeting and an overview of molecular cellular pathology. We recently performed an analysis of protein biomarkers in COVID-19 [ 30 ]; this labour-intensive approach produced similar data to the methodology we describe here. Thus, we have created a paradigm for such research which is easy to use and apply, and demonstrated its utility.…”
Section: Discussionmentioning
confidence: 99%